Microsoft Visual C++ - Álvarez Martínez, Noé (My University, 1995)
What are objects? As the phrase implies, objects are the basis for object-oriented programming. The notion of an objects is familiar to all of us, and it translates well to the world of programming. For our purposes, an object has an identity. It is defined by its attributes (data elements) and behaviors (functions) An object's attributes and behaviors make it distinct from other objects. In the language of object-oriented programming, objects represent things such as rectangles, ellipses, and triangles, as well as moner, part numbers, and items in inventory.
Keywords: object-oriented analysis; using inheritance; managing complex projects; using arrays; The debugger; using Cstring; formatting and file; memory management; conversions